2023
DOI: 10.1039/d2dt03201e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of amphiphilic chiral salen complexes and their conformational manipulation at the air–water interface

Abstract: A series of amphiphilic salen complexes, [L1a,bM] and [L2a,bM], were designed and synthesized. These complexes consist of two or four hydrophilic triethylene glycol (TEG) chains and the hydrophobic π-extended metallosalen...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Although there are few reported cases in which the conformation of binaphthyl molecules is controlled at the air – water interface, a change in the molecular arrangement has been observed for binaphthyl molecules with carboxylic acids as hydrophilic moieties upon compression [ 33 ]. In addition, S. Akine et al reported an attempt to control the molecular conformation of salen complexes with axial chirality at the air – water interface [ 31 ].…”
Section: Molecular Machine At Air – Interfacementioning
confidence: 99%
“…Although there are few reported cases in which the conformation of binaphthyl molecules is controlled at the air – water interface, a change in the molecular arrangement has been observed for binaphthyl molecules with carboxylic acids as hydrophilic moieties upon compression [ 33 ]. In addition, S. Akine et al reported an attempt to control the molecular conformation of salen complexes with axial chirality at the air – water interface [ 31 ].…”
Section: Molecular Machine At Air – Interfacementioning
confidence: 99%